Clinical significance of miR-3178 in non-small cell lung cancer patients: miR-3178 in NSCLC: Clinical Significance - Yu, Haizhen; Li, Shizhen (Journal of Medical Biochemistry, 2026)
Background & objectives：Non-small cell lung cancer (NSCLC) is a malignant tumor with high morbidity and mortality, with low survival rate and poor prognosis This study aims to explore the diagnostic and prognostic value of miR-3178 in NSCLC.Methods: Study included 118 NSCLC patients and 97 healthy subjects. RT-qPCR measured miR-3178 and MIB2 in serum or cell lines. χ2 tests linked miR-3178 to clinicopathological features. ROC, Kaplan-Meier, and Cox analyses evaluated diagnostic and prognostic significance of miR-3178 and MIB2.Results: Compared to the control group, the expression level of miR-3178 was significantly reduced, while MIB2 expression was notably elevated in NSCLC patients. The expression of miR-3178 is significantly correlated with the TNM stage and LNM in NSCLC patients. NSCLC patients with higher miR-3178 expression levels exhibit significantly higher 5-year overall survival rates. Furthermore, TNM stage, miR-3178 expression, and MIB2 expression are independent risk factors that influence the prognosis of NSCLC. MIB2 serves as a target gene of miR-3178, and their expression levels display a significant negative correlation. When diagnosing NSCLC solely based on miR-3178, the AUC is 0.838; for MIB2 alone, the AUC is 0.818; however, when miR-3178 and MIB2 are combined for diagnosis, the AUC increases to 0.903.Conclusion: The downregulation of miR-3178 and upregulation of MIB2 are associated with the progression and deterioration of NSCLC patients, indicating poor prognosis. miR-3178 targets MIB2, and their combined diagnosis can enhance the diagnostic value for NSCLC, potentially reducing the risk of adverse outcomes.
Keywords: non-small cell lung cancer, miR-3178, MIB2